2010
DOI: 10.1117/12.868599
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study on the generation of THz sub-comb via surface-emitted optical rectification of ultra-short pulse in periodically poled lithium niobate

Abstract: In this paper, we proposed a method for THz sub-comb generation based on optical rectification. The result of our calculation indicated that THz pulse train, generated by surface-emitted optical rectification (OR) of femtosecond (fs) laser pulse in a periodically poled lithium niobate (PPLN), has a comb-like spectrum. The theoretical analysis was based on radiating antenna model. The characteristic of this THz sub-comb was analyzed both in frequency and time domain.The mechanism of this phenomenon was explaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Our theoretical result indicated that a periodical train of THz pulses with a comb-like spectrum could be obtained, if the parameters are designed properly [31]. We also investigated p-polarized Cherenkov radiation and designed Brewster-cut geometry, which can provide high coupling efficiency, high intensity and good beam quality [32].…”
Section: Broadband Cherenkov Radiation Based On Ormentioning
confidence: 94%
“…Our theoretical result indicated that a periodical train of THz pulses with a comb-like spectrum could be obtained, if the parameters are designed properly [31]. We also investigated p-polarized Cherenkov radiation and designed Brewster-cut geometry, which can provide high coupling efficiency, high intensity and good beam quality [32].…”
Section: Broadband Cherenkov Radiation Based On Ormentioning
confidence: 94%